Determinants of Profit in Local Creative Bag UMKM Production: Penentu Keuntungan dalam Produksi UMKM Tas Kreatif Lokal - Murtafi’a, Lutfi Ainun; Rahmawati , Imelda Dian (Indonesian Journal of Law and Economics Review, 2025)
Background: UMKM play a crucial role in supporting local economic growth, making profit analysis essential for business sustainability. Specific Background: Local bag-production UMKM face fluctuations in production costs, marketing expenses, and sales volume, which directly shape profitability. Knowledge Gap: However, limited studies have examined these three variables simultaneously within the context of small-scale creative industries. Aim: This study aims to analyze how production costs, marketing costs, and sales volume contribute to UMKM profit. Results: The findings show that production costs and marketing costs have measurable statistical relationships with profit, while sales volume emerges as the most influential determinant of financial outcomes. Novelty: This research offers new insight by focusing on a specific local bag-production UMKM with unique cost structures and operational constraints. Implications: The study highlights the importance of optimizing cost efficiency and strengthening sales strategies to support sustainable profit growth for similar creative UMKM sectors. Highlights:• Significant factors determining UMKM profit• Sales volume as primary profit determinant• Cost structures shaping financial outcomes Keywords: UMKM, Production Cost, Marketing Cost, Sales Volume, Profitability